Entrepreneurial finance finance and business strategies for the serious entrepreneur - Rogers, Steven 1957- (McGraw-Hill Education, 2014)
A guide to setting up and managing your business' finances. It offers potent methods for keeping firm financial control of your enterprise and insightful tips for avoiding the multitude of financial barriers that may block your entrepreneurial dream.
Includes bibliographical references and index. - Print version record
Keywords: Business enterprises -- Finance; Business planning; Entrepreneurship; Entrepreneuriat; entrepreneurs; Business enterprises; Finance